2005
DOI: 10.1111/j.1475-682x.2005.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

The Boundaries of Difference: Negotiating Gender in Recreational Sport*

Abstract: There is a pervasive belief that meaningful gender differences structure the abilities and desires of bodies. These gender differences are presented as categorical imperatives, despite the prevalence of a range of abilities and desires across genders. How are beliefs about gender differences maintained in light of increasing challenges? Adult recreational sports provide an interesting subworld in which to investigate this question. Through an ethnography of coed softball, reactions to women's demonstrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 12 publications
(17 reference statements)
2
37
1
Order By: Relevance
“…With some recent exceptions (Guérandel & Mennesson, 2007;Lökman, 2010;McNaughton, 2012;Spencer, 2011), there has been relatively little attention to sex-integrated training, much less direct focus on its transformative potential. Yet in other physical cultural settings, feminist scholars have explored mixed-sex participation, suggesting that personal empowerment, along with broader challenges to hierarchal gender discourse, can be strengthened immensely when men and women jointly experience the potentials of differently sexed bodies (Anderson, 2009;McDonagh & Pappano, 2008;Travers, 2008;Wachs, 2005). This indicates that investigating mixed-sex training might yield richer analyses of the transformative value of women's involvement in martial arts; a task we turn to in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…With some recent exceptions (Guérandel & Mennesson, 2007;Lökman, 2010;McNaughton, 2012;Spencer, 2011), there has been relatively little attention to sex-integrated training, much less direct focus on its transformative potential. Yet in other physical cultural settings, feminist scholars have explored mixed-sex participation, suggesting that personal empowerment, along with broader challenges to hierarchal gender discourse, can be strengthened immensely when men and women jointly experience the potentials of differently sexed bodies (Anderson, 2009;McDonagh & Pappano, 2008;Travers, 2008;Wachs, 2005). This indicates that investigating mixed-sex training might yield richer analyses of the transformative value of women's involvement in martial arts; a task we turn to in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined issues of gender expectations and doing gender in softball (Wachs 2002(Wachs , 2005Malcom, 2003). Wachs (2002) examined the gendered nature of the rules that are used in co-ed softball.…”
Section: Gender and Softball Rulesmentioning
confidence: 99%
“…However, both the reactions of the men and their statements indicate that men do not share this belief that women can hit middle intentionally or that it is not problematic when they do so. Wachs (2005) found that superlative performances by female softball players were interpreted in ways that undermined their competence. Outstanding plays were attributed to luck or contextualized as being "good for a girl".…”
Section: Role Of Gender In Co-ed Softball -The Battermentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, she argues that if women are Other, then sport and women are necessarily mutually exclusive (see also, Scott and Derry, 2005). Sport, therefore, remains one area where gender boundaries are carefully drawn and policed (Shogan, 1999;Wachs, 2005;Woodward, 2009). The firm conviction that women's bodies have different, and lesser, abilities compared to men underpins this adherence to gender binaries (Wachs, 2005:527), holding in place the (white) male body as the archetypical sporting body, and as the standard against which other sporting performances can be measured.…”
Section: From Mind-body To the 'Shifted Sensorium'mentioning
confidence: 99%